KEPENTINGAN KOREA SELATAN DALAM KERJASAMA INVESTASI MINYAK DENGAN IRAN 2014-2016 - Muhammad Iqbal; Muhammad Saeri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to explain the limitations of South Korea in its oil energy resources which can be fully utilized to meet the needs of its industrial level. South Korea is not an oil producing country, the maximum it has ever managed to produce from the Donghae-1 natural gas field through the efforts of the Korea National Oil Corporation (KNOC) is only 1,000 b/d of ultra-light crude oil. (condensate), as a substitute for a negligible portion of the total oil consumption of 2.4 million b/d per day. How it has managed to feed growing giants such as Hyundai, LG, Daewoo, GoldStar, KIA, and Samsung among other high energy consumption industries over the years, is worth knowing. A more interesting part of this effort is South Korea's ability to export refined petroleum products such as sulfur diesel, kerosene and others in intermediate distillates including, gasoline, and jet fuel to countries such as Vietnam. Alternative energy sources such as electricity, biofuels, natural gas and unrelenting investment in exploration and production across all continents of the world remain a secret.This study uses the concept of international cooperation and the theory of Foreign Direct Investment, as well as using data collection techniques through document analysis or analyzing secondary data, such as books, journals, reports, and websites, the theory used explains how international cooperation and how foreign direct investment is running.Keywords:: KOREA SELATAN, KNOC, KOGAS, JCPOA, NIOC, NIGC, IRAN, DOPCO, KEPCO.